2011
DOI: 10.1113/expphysiol.2011.058388
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin depolarizes mitochondria in isolated myometrial cells

Abstract: Oxytocin is known to play important roles in uterine contractionsand resultant dissipation of the mitochondrial electrochemical gradient. ATP synthase is also stimulated, which would further contribute to a decrease in ψ m .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Apparently this parameter is more sensitive to oxytocin-effect induced by 10 nM was not exceeded by higher doses. Stimulating effect of oxytocin on mitochondrial activity is in keeping with other studies demonstrating depolarizing effect of oxytocin on mitochondria in isolated myometrial cells (Gravina et al 2011) and results of Alizadeh et al (2010) which found cardioprotective effects of oxytocin mediated by mitochondrial ATP-dependent potassium channels. No protective effect of oxytocin was observed in a peroxide model of oxidative stress.…”
Section: Discussionsupporting
confidence: 54%
“…Apparently this parameter is more sensitive to oxytocin-effect induced by 10 nM was not exceeded by higher doses. Stimulating effect of oxytocin on mitochondrial activity is in keeping with other studies demonstrating depolarizing effect of oxytocin on mitochondria in isolated myometrial cells (Gravina et al 2011) and results of Alizadeh et al (2010) which found cardioprotective effects of oxytocin mediated by mitochondrial ATP-dependent potassium channels. No protective effect of oxytocin was observed in a peroxide model of oxidative stress.…”
Section: Discussionsupporting
confidence: 54%
“…Other, yet unidentified, physiological and pathological factors likely will be found to directly or indirectly activate or block the activity of the mitoK ATP channel. Mitochondria depolarize under normal conditions (121) and naturally occurring substances, such as oxytocin depolarize mitochondria in myometrial cells by either direct or indirect mechanisms (68).…”
Section: Mitochondrial Depolarization and Related Signaling Eventsmentioning
confidence: 99%
“…; Gravina et al . ). This could comprise an alternative explanation (given the reduction in mtDNA copy number) for our observations showing that myometrium from older pregnant mice has altered contractility in vitro .…”
Section: Discussionmentioning
confidence: 97%